Heterocyclic iodoniums as versatile synthons to approach diversified polycyclic heteroarenes. Issue 57 (16th October 2019) - Zhu, Daqian; Wu, Zhouming; Liang, Liyun; Sun, Yameng; Luo, Bingling; Huang, Peng; Wen, Shijun
Abstract : The transformation of heterocyclic iodoniums led to the construction of heterocycles with a high structural diversity. Abstract : Polycyclic heteroarenes are important scaffolds in the construction of pharmaceuticals. We have previously developed a series of novel heterocyclic iodoniums. In our current work, these unique iodoniums were employed to construct various complex polycyclic heteroarenes with structural diversity via tandem dual arylations. As a result, indole, thiophene and triphenylene motifs were fused into these heterocycles with high molecular quality, which might provide promising fragments in drug discovery. Moreover, these heterocycles could be diversified at a late stage.